2020
DOI: 10.1021/acsomega.0c00015
|View full text |Cite
|
Sign up to set email alerts
|

Development and Mechanical Characterization of HGMS–EHS-Reinforced Hollow Glass Bead Composites

Abstract: Hollow glass microsphere-reinforced epoxy hollow spheres (HGMS–EHSs) were prepared by a “rolling ball method” using expanded polystyrene beads, HGMSs, and epoxy resin (EP). The three-phase epoxy syntactic foam (epoxy/HGMS–EHS–HGMS composite) was fabricated by combining HGMS–EHS as a lightweight filler with EP and HGMS by a “molding method”. The HGMS–EHS and epoxy curing agent systems were well mixed by scanning electron microscopy. Experiments show that higher HGMS–EHS stack volume fraction, lower HGMS–EHS lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…As a result, all the composites revealed a decrease in density values as the HGM content increased. Similar trends can be observed in [14,[28][29][30]. Furthermore, HGM/E composites revealed lower density as compared with HGM/CNT/E and HGM/G/E.…”
Section: Densitysupporting
confidence: 80%
“…As a result, all the composites revealed a decrease in density values as the HGM content increased. Similar trends can be observed in [14,[28][29][30]. Furthermore, HGM/E composites revealed lower density as compared with HGM/CNT/E and HGM/G/E.…”
Section: Densitysupporting
confidence: 80%
“…Figure 3(d) is the graph of the difference in compressive strength of GF‐ESF and ESF. Compared with Tao Jiang etc., [21] the compressive strength of epoxy syntactic foam filled with GF is increased by 69 %, and the unfilled foam is also increased by 56 %. It can be seen from the figure that the compressive strength of each GF‐ESF is greater than that ESF, and as the density of HGMS‐EHS increases, the difference becomes more and more obvious.…”
Section: Resultsmentioning
confidence: 96%
“…There is no obvious interfacial debonding between CFF/EP layer and HGB/EP layer. In addition, HGB, a rigid particle, hollow sphere shape (as shown in Figure 7A, B), can carry the load and disperse the stress, [ 17 ] contributing to the strengthening to a certain degree. Therefore, it can be concluded that the flexural strength and modulus of CFF/HGB/EP sandwich composite laminates improved with the HGB content increasing.…”
Section: Resultsmentioning
confidence: 99%
“…However, the impact strength decreases when HGB content exceeds a certain value, resulting from two main reasons. On the one hand, HGB are inorganic rigid particles, [ 17 ] so that the increase in HGB content will reduce the toughness and increase the brittleness of the sandwich composite. When subjected to impact load, the failure mode of composite will transform ductile fracture into brittle fracture, resulting in a decrease in impact strength.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation